Executive Committee Minutes 2015-11-19 - Academic Senate:::::::::
Chair Report. Agenda – Approved. Minutes of 11/5/15 – Approved. Revision to the Political Science minor approved for Senate consent calendar. President Report. Vice Chair Report. Vice President of Administration and Finance Report. EPC Report. Title IX Task Force. Revision to the Career Minor in Arts Mgmt approved for Senate consent calendar. FSAC Report. Associated Students Report. RTP Revisions summary document approved as information item for Senate. Revised APC charge and name referred back to Structure and Functions. Senate Agenda approved.